2017
DOI: 10.6061/clinics/2017(08)08
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Health Economic Evaluations of Diagnostic Tests in Brazil: How accurate are the results?

Abstract: The aim of this study is to identify and characterize the health economic evaluations (HEEs) of diagnostic tests conducted in Brazil, in terms of their adherence to international guidelines for reporting economic studies and specific questions in test accuracy reports. We systematically searched multiple databases, selecting partial and full HEEs of diagnostic tests, published between 1980 and 2013. Two independent reviewers screened articles for relevance and extracted the data. We performed a qualitative nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In Saudi Arabia, which had the highest number of economic evaluations in our review, a study found that only 61 randomized trials were published between 1987 and 2018. 37 Unavailability of data has been reported as a major barrier for researchers to conduct health economics research, 32 , 38 which reflects the reason behind the limited number of studies in this review.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, which had the highest number of economic evaluations in our review, a study found that only 61 randomized trials were published between 1987 and 2018. 37 Unavailability of data has been reported as a major barrier for researchers to conduct health economics research, 32 , 38 which reflects the reason behind the limited number of studies in this review.…”
Section: Discussionmentioning
confidence: 99%